Optics Learning Transformation through Project-Based Learning: Enhancing Scientific Abilities and Affective Learning Outcomes in Students with the Pinhole Camera Project - Fadilah, Nur; Nurlaela, Ai; Romadhon, Dzikri Rahmat (Jurnal Pendidikan Fisika, 2024)
In physics education, the topic of optics requires a thorough and detailed understanding due to its challenging and intangible nature. To help students learn physics through practice, it is necessary to enhance their scientific abilities. Additionally, learning outcomes serve as a benchmark for success in education. In this context, project-based learning is chosen as the instructional model for presenting optics material in the classroom, since several studies have found this model to be effective in teaching. This research aims to measure the improvement of scientific abilities and affective learning outcomes of students in the field of physics, specifically the topic of optics. The quasi-experimental design method was employed in this study. The research sample comprised 11th-grade science students divided into two groups: the control group using which employed an inquiry-based learning model and the experimental group which utilized a combination of inquiry-based learning and project-based learning. The final project for the applied teaching model involved a pinhole camera. Data was gathered using observation sheets and questionnaires and subsequently analyzed using non-parametric tests (Mann-Whitney U and Wilcoxon). The data analysis results revealed a significant value (<0.001), demonstrating that the project-based learning model effectively enhanced students’ scientific abilities and affective learning outcomes, highlighting marked improvements in the experimental class compared to the control class. Additionally, the project-based learning model proved effective in engaging students actively, creating a more effective and interactive learning experience. Students also expressed greater interest in physics, as lessons incorporated practical activities rather than solely focusing on theoretical concepts.